Main factors controlling stable production from gas-condensate reservoirs in block 2 of the Shunbei Oilfield, Tarim Basin - Chen, Shuyang; Mei, Shengwen; Huang, Cheng; Chen, Wen; Zhang, Lei; Shang, Haojie; Xie, Pengfei (Frontiers in Earth Science, 2025)
Condensate gas reservoirs in the second area of the Shunbei Oilfield in the Tarim Basin, China have undergone multiple stages of tectonic movements, resulting in complex structural patterns and reservoir characteristics. These reservoirs face significant development challenges, including rapid production decline, limited reservoir reconstruction methods, and weak well pattern control capabilities. To enhance their stable production capacity, this study employs a comprehensive approach involving geological analysis, seismic reflection characteristics research, geological data analysis, and bottom water discrimination methods to systematically investigate the Shunbei condensate gas reservoir. The results indicate that structural characteristics significantly influence the formation of reservoirs and the distribution of oil and gas reserves. Long-term fault activity is conducive to the development of large-scale reservoirs. Reservoir connectivity and physical properties play a crucial role in production performance. Optimizing reservoir reconstruction parameters can enhance both production and stable production capacity of oil and gas wells. However, sealed water conditions during development and strong bottom water presence are unfavorable for production capacity. Based on these findings, a quantitative evaluation index system for assessing the stable production capacity of carbonate reservoirs has been successfully established. This system clarifies the importance and weight relationships of factors such as fracture activity intensity, fracture background, and water body influence. The system has been validated through its application in the No. 4 and No. 8 belts, although practical application still requires careful consideration of the complex geological conditions. The research outcomes provide a critical foundation for evaluating the stable production capacity of carbonate reservoirs and formulating effective oil and gas field development strategies. These insights contribute to improving the overall efficiency and sustainability of oil and gas field developments.